Determinants of outward foreign direct investment from BRIC countries: an explorative study - Holtbrügge, Dirk; Kreppel, Heidi (International Journal of Business and Emerging Markets, 2012)
WiSo-Import:2015-03-26:2853

Employer Attractiveness of Chinese, Indian and Russian Firms in Germany: Signaling Effects of HR Practices - Holtbrügge, Dirk; Kreppel, Heidi (Corporate Reputation Review, 2015)

Können Musikgeschmack und Reisepräferenzen die kulturelle Anpassung von Auslandsentsandten vorhersagen? Ergebnisse einer empirischen Untersuchung - Holtbrügge, Dirk; Kreppel, Heidi; Puck, Jonas (Zeitschrift für Management, 2008)
Die kulturelle Anpassung von Auslandsentsandten ist eine wesentliche Voraussetzung für einen erfolgreichen Auslandseinsatz. Trotz zahlreicher Studien der Faktoren, welche die kulturelle Anpassung begünstigen, ist dieses Forschungsfeld immer noch durch einen Mangel an gesicherten Erkenntnissen geprägt. Die vorliegende Studie betrachtet zwei bislang noch nicht thematisierte Faktoren, nämlich den Musikgeschmack und die individuellen Reisepräferenzen, und testet deren Einfluss auf die kulturelle Anpassung von 140 Auslandsentsandten in Lateinamerika. Eine Regressionsanalyse zeigt einen signifikanten Einfluss der Präferenz für Folk- und Weltmusik sowie für Erlebnisreisen auf. Diese Präferenzen können im Auswahlprozess von Entsandten als relativ leicht messbare Selektionskriterien eingesetzt werden.
WiSo-Import:2015-03-26:434
Keywords: Economics/Management Science; Innovation

Perceptions of Chinese and Indian Brand Personalities in Germany - Holtbrügge, Dirk; Kreppel, Heidi (Multinationals and Global Consumers. Tension, Potential and Competition, 2013)
WiSo-Import:2015-04-20:5089

The Perceived Attractiveness of Chinese Products by German Consumers - A Sociopsychological Approach - Kreppel, Heidi; Holtbrügge, Dirk (Journal of Global Marketing, 2012)
The presence of Chinese companies in international markets has increased, and one of their main challenges is to overcome the negative image that Chinese products have in many countries. This study aims to shed light on how sociopsychological determinants affect the perceived attractiveness of Chinese products in Germany, using a sociopsychological approach based on social identity theory and social learning theory. The results indicate that the individual's age, level of education, occupational status, and international experience have significant effects on the perceived attractiveness of Chinese products, whereas the individual's international experience in China does not show such effects. Significant differences between different product categories are revealed. © 2012 Copyright Taylor and Francis Group, LLC.
WiSo-Import:2015-03-26:3919
Keywords: Chinese outward FDI; Chinese products; country of origin; perceived attractiveness; social identity theory; social learning theory

Российские многонациональные корпорации в Германии: имидж бренда и привлекательность работодателя" (Russian Multinationals in Germany: Brand Image and Employer Attractiveness) - Holtbrügge, Dirk; Kreppel, Heidi (Вестник Санкт-Петербургского университета. Серия “Менеджмент", 2012)
WiSo-Import:2015-03-26:3975